Investigação da usinabilidade do açoinoxidável duplex UNS 32205 no microfresamento - Silva, Letícia Cristina (2017)
The increasing demand for products requiring increasingly smaller components drives the development of micromachining, which is considered to be highly necessary for technological advances in the field of mechanical engineering. In this context, micromilling is a viable alternative for the manufacture of these microcomponents, allowing the machining of complex geometries in various materials such as: metals and alloys, composites, polymers, ceramics and some stainless steels, the latter of which arouse great interest for the industry due to its characteristic of great resistance to corrosion and oxidation. However, adapting the knowledge of milling of stainless steels on a conventional scale to the microscale requires an understanding of the specific phenomena that arise with the reduction of operations. Considering this context, this work has as main objective the investigation of the machinability of duplex stainless steel UNS S32205 in the micromilling operation. For that, tests were made to manufacture microchannels, using a 4-axis CNC micromill machine tool, with maximum spindle rotation of 60 000 rpm and resolution of 0.1 μm, using 200 µm and 400 µm diameter tools. From the experimental data, it was investigated the evolution of tool wear, the forms and mechanisms of tool wear, burr formation, machined surface quality, surface roughness and chip formation. The results show that the tool with diameter 200 µm presented an excellent performance in relation to the machined length, however the increased cutting speed led to excessive wear and high burrs. In the machining tests using tools with diameter 400 µm, the wear and height of the burrs was attenuated through the use of cutting fluid. Finally, the tools with the largest diameter presented minor burrs when compared to the smaller diameter, forming continuous chips, in addition to presenting a lower chip thickness ratio of the chips.